HOW POPULAR IS SOCIAL MEDIA IMAGE GRATIFICATION AS A RESEARCH THEME IN TOP JOURNALS? - Che Ilias, Irma Syarlina; Ramli, Suzaimah; Wook, Muslihah; Hasbullahi, Nor Asiakin (Malaysian Journal of Computer Science, 2021)
Understanding why people use social media provides an insight into the nature of behaviours in social networking where sharing images or photos and like other users’ posts are some preferred social media user’s behaviours. Theory of Uses and Gratifications posits that the audience actively chooses a type of media that suits their needs. Motivations are explained by the questions of why users use social media and what gratifications they derive from their use, and whether they prefer to use images rather than texts or even videos. Prior studies found that there are distinctly different gratifications resulting from the use of images in social media. This research paper hereby explores a thematic review of the top journals regarding the motives of image use in social media from the year 2017 to 2020. The strategy of the research was to investigate through a comprehensive number of review articles on the images used in social media and the result was then analysed. From the literature, the findings of the code-to-document report have highlighted several research patterns or themes in the motives of image use in social media. The results benefit the future direction of later research and narrow the gap between research solutions on image use in social media in the context of gratifications.